2022
DOI: 10.1007/s00424-022-02672-0
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral periaqueductal gray matter integrative system of defense and antinociception

Abstract: Defensive responses are neurophysiological processes crucial for survival during threatening situations. Defensive immobility is a common adaptive response, in rodents, elaborated by ventrolateral periaqueductal gray matter (vlPAG) when threat is unavoidable. It is associated with somatosensory and autonomic reactions such as alteration in the sensation of pain and rate of respiration. In this study, defensive immobility was assessed by chemical stimulation of vlPAG with different doses of NMDA (0.1, 0.3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…157,211,219,220,223,224 The PAG plays an important restorative role to compensate for respiratory distress and in other exigent behavioral situations that require enhanced respiration and arousal; electrical or glutamatergic stimulation of the PAG will result in increases in respiration. 221,[225][226][227][228] There are anatomical connections between the PAG, amygdala, and dorsal raphe, and PAG neurons express several 5-HT receptor subtypes. 229,230 Functional neuroimaging studies show significantly elevated postictal PAG neural activity in DBA/1 mice.…”
Section: Periaqueductal Graymentioning
confidence: 99%
See 1 more Smart Citation
“…157,211,219,220,223,224 The PAG plays an important restorative role to compensate for respiratory distress and in other exigent behavioral situations that require enhanced respiration and arousal; electrical or glutamatergic stimulation of the PAG will result in increases in respiration. 221,[225][226][227][228] There are anatomical connections between the PAG, amygdala, and dorsal raphe, and PAG neurons express several 5-HT receptor subtypes. 229,230 Functional neuroimaging studies show significantly elevated postictal PAG neural activity in DBA/1 mice.…”
Section: Periaqueductal Graymentioning
confidence: 99%
“…The PAG is strongly implicated in enhancement of respiratory function and arousal in humans and animals 219–221 and has been suggested to function as a central “suffocation alarm.” 222 This action is mediated by its projections to the hypothalamus and RVLM that are involved in control of respiration 157,211,219,220,223,224 . The PAG plays an important restorative role to compensate for respiratory distress and in other exigent behavioral situations that require enhanced respiration and arousal; electrical or glutamatergic stimulation of the PAG will result in increases in respiration 221,225–228 . There are anatomical connections between the PAG, amygdala, and dorsal raphe, and PAG neurons express several 5‐HT receptor subtypes 229,230 .…”
Section: Brain Structures Implicated In Sudepmentioning
confidence: 99%
“…The PAG (also termed the central gray), especially the ventral lateral PAG (VLPAG: Fig. 7 M) in the midbrain, is a major descending modulation center of pain [ 53 ]. Here, the VLPAG region of the SCI rats showed higher mean IRL of GFAP and Iba1/TNFα co-staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The power of a positive environment cannot be underestimated when it comes to treating fear‐related psychiatric disorders (Imanaka et al., 2006). Indeed, it was demonstrated that several limbic structures involved with defensive behaviors and related emotions in mammals (de Mello et al., 2022; Graeff, 1994; Ullah et al., 2015) are recruited to regulate the amelioration of environmental enrichment and cue in fear behavior in an animal model of post‐traumatic stress disorder (Yu et al., 2022), and there is evidence for enhancement of hippocampal neurons in adult rodents submitted to an environment enrichment (Kempermann et al., 1997). Controversely, a decrease in hippocampal volume was also reported in a mouse experimental model of post‐traumatic stress disorder (Golub et al., 2011).…”
Section: Introductionmentioning
confidence: 99%